A new species of Physalaemus (Anura, Leptodactylidae) from the Atlantic Forest of Misiones, northeastern Argentina - Cardozo, Dario E.; Pereyra, Martin O. (Zootaxa, 2018)
A new species of Physalaemus from Misiones province, Argentina, in the Atlantic forest domain is described. The new species is a member of the P. gracilis group, based on its phylogenetic position and the occurrence of a putative morphological synapomorphy (occurrence of an unpigmented median stripe on throat, chest, and/or abdomen). Physalaemus sp. nov. is characterized by a long advertisement call composed of non-pulsed notes with slightly descendant modulation, large size (mean SVL = 32.0 mm males, 34.0 mm females), slender body aspect, head longer than wide, supratympanic fold developed, an unpigmented median stripe on venter, medium sized inguinal glands, tarsal tubercle present, and supernumerary tubercles on hands and feet, which are character states that combined distinguish the new species from all the members of the genus. In this study, we provide its formal description based on external morphology, advertisement call, and 16S genetic distance. In addition, the distribution ranges for the new species and P. gracilis are revisited, the advertisement call of P. gracilis is redescribed, and a discussion about the available names which could be applicable to the new species is provided.